DFT insights into the electronic structure, mechanical behaviour, lattice dynamics and defect processes in the first Sc-based MAX phase Sc2SnC - M. A. Hadi; S.-R. G. Christopoulos; A. Chroneos; S. H. Naqib; A. K. M. A. Islam (Scientific Reports, 2022)
Abstract Here we employed the density functional theory calculations to investigate some physical properties of first Sc-based MAX phase Sc2SnC including defect processes to compare with those of existing M2SnC phases. The calculated structural properties are in good agreement with the experimental values. The new phase Sc2SnC is structurally, mechanically and dynamically stable. Sc2SnC is metallic with a mixture of covalent and ionic character. The covalency of Sc2SnC including M2SnC is mostly controlled by the effective valence. Sc2SnC in M2SnC family ranks second in the scale of deformability and softness. The elastic anisotropy level in Sc2SnC is moderate compared to the other M2SnC phases. The hardness and melting point of Sc2SnC, including M2SnC, follows the trend of bulk modulus. Like other members of the M2SnC family, Sc2SnC has the potential to be etched into 2D MXenes and has the potential to be a thermal barrier coating material.